Theorizing Strategic Communication in Parsimony from the U.S. Government Perspective - Young Joon Lim (KOME: An International Journal of Pure Communication Inquiry, 2015)
Although the term Strategic Communication seems to be a rising topic in communication studies, it is obvious that the term has been hardly visualized and explained from the U.S. government perspective in academic work. This paper theoretically visualizes strategic communication processes. The Department of State and the Department of Defense streamlined the use of strategic communication in different terms but they both focus on using soft power over hard power to gain support from foreign audiences through communication. Both departments especially after the 9/11attacks have developed programs to win hearts and minds of the target audience. This paper shows the salient process of strategic communication programs and conceptualizes principles of strategic communication from their perspectives. This paper after all illustrates the processes for theorizing strategic communication.